Efektivitas Membaca Nyaring Dialogis terhadap Pemahaman Inferensial Siswa Kelas V Sekolah Dasar - Aprinawati, Iis; Ayu, Citra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Inferential comprehension is a critical component of upper-elementary reading literacy because it requires students to integrate explicit textual information with prior knowledge in order to construct implied meaning. However, classroom reading instruction often remains focused on literal understanding, limiting students’ opportunities to practice drawing inferences, interpreting characters’ motives, and establishing causal coherence across a text. This study aimed to examine the effectiveness of dialogic read-aloud in improving fifth-grade students’ inferential comprehension. A classroom-based quasi-experimental design was employed using a pretest–posttest comparison between an experimental group and a control group. The study was conducted with Grade 5 students in two public elementary schools—SDN 006 and SDN 004 Langgini, Bangkinang. The intervention implemented dialogic read-aloud through narrative/children’s literature texts accompanied by open-ended prompts, prediction, clarification, and elaborative feedback, while the control group received conventional reading instruction. The findings indicate that students exposed to dialogic read-aloud demonstrated stronger gains in inferential comprehension than those in the control condition, reflected in improved ability to generate inferences, justify interpretations of characters’ actions, and articulate moral messages in an evidence-based manner. These results suggest that dialogic read-aloud is a promising instructional approach for enhancing higher-order reading literacy and strengthening Indonesian language instruction in upper elementary classrooms.